Impacts of sea temperature rise on Rastrelliger kanagurta potential fishing grounds in the Exclusive Economic Zone (EEZ) off South China Sea - Kamaruzzaman Y.N.,; Mustapha M.A.,; Ghaffar M.A., (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Indian mackerel (Rastrelliger kanagurta) is one of the most commercially crucial epipelagic scombrid where it is caught in the Exclusive Economic Zone (EEZ) off the South China Sea (SCS). High demand for fisheries resources is a challenge for fishers to achieve optimal fish landing targets. By using R. kanagurta catch data, and high resolution satellite data of chl-a and SST (MODIS-Aqua) and SSH (AVISO) from 2018 together with boosted regression tree (BRT) model, this study aims to determine the impact of sea surface temperature (SST) increase on the potential catch of R. kanagurta based on temperature projection of IPCC-AR5-RCPs scenarios. BRT modelling result indicated that during the northeast monsoon (NEM), at elevated temperature of 1.80 and 2.60 ℃ showed that the potential fishing grounds of R. kanagurta increase in the area especially in the northern part of the EEZ. However, at elevated temperature of 3.30 ℃, the potential fishing areas was found to decrease along the coast of Peninsular Malaysia. Meanwhile, during southwest monsoon (SWM) and inter-monsoon transition, at temperature rise of 1.80, 2.60 and 3.30 °C showed a significant reduction in the potential fishing area of the R. kanagurta potential fishing grounds especially along the coast of the EEZ off SCS. Results indicated that changes in SST influenced suitability of habitat which affected the distribution of R. kanagurta. Understanding the impacts of temperature increase would contribute towards future sustainable fisheries resource management strategies.